The Cold War in the chapter “The giant in red boots”, from the series The tales of Broca street. Analysis of a cognitive model - Pardo Fernández, Rodrigo; Morales Campos, Arturo (Acta Universitaria, 2022)
In this paper we intend to show, under the guidelines of sociosemiotics, the political function of the episode “El gigante de las botas rojas”, of the television series Los cuentos de la calle Broca, broadcast in Mexico through Canal Once in the 90s. For sociosemiotics, every cultural object is an ideological tool that can be used with "instructive" and dominant intentions. In the case of texts (literary, cinematographic, television, etc.) aimed at a supposedly children’s audience, the manipulation of information is sometimes greater. For certain characteristics observed in its vision and for the moment in which it is produced in France (1995), and transmitted in that country and in Mexico, we start from the hypothesis that this chapter transcribes part of the western ideology (capitalist-Catholic) aiming to juxtapose it with the social ideology. The analysis of certain signs (linguistic, vestimental, iconic, etc.) will allow us to understand their significant function from this assumption. The result of this analysis will contain common notions at the time of production of the episode in question. In this way, we argue that "The giant of the red boots" functions as an instructive cognitive model, since it implies a way of understanding and acting before reality.